Evaluation of the Use of Digital Technologies to Improve Case Management of Uncomplicated Malaria by Community Pharmacists in Nigeria (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Malaria remains a tropical disease of public health concern. Treating malaria infection without parasitological diagnosis and follow-up yields poor outcomes.Objectives:  This study assessed knowledge, attitudes, use of Malaria Rapid Diagnostic Tests (mRDTs), and evaluated impact of a mobile health intervention on case management by community pharmacists.Materials and Methods: The mixed - method study enrolled 112 community pharmacists in Kwara State Nigeria, randomized into control and intervention groups (n = 56 each). Same validated questionnaires were used to obtain baseline and post-intervention data. Only intervention group received educational YouTube videos, mRDT kits and twice-weekly short message service follow-up for six months. Pre- and post- intervention scores were measured and compared in both groups using Mann-Whitney U and t-tests at p